2022
DOI: 10.1111/bcpt.13761
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ciprofol (HSK3486) versus propofol for the induction of deep sedation during gastroscopy and colonoscopy procedures: A multi‐centre, non‐inferiority, randomized, controlled phase 3 clinical trial

Abstract: Ciprofol is a propofol analogue with improved pharmacokinetic properties. A multi-centre, non-inferiority trial was conducted to compare the deep sedation properties of ciprofol and propofol with a non-inferiority margin of 8% in patients undergoing gastroscopy and colonoscopy. In total, 289 patients were randomly allocated for surgery (259 colonoscopy and 30 gastroscopy) at a 1:1 ratio to be given intravenous injections of ciprofol (0.4 mg/kg) or propofol (1.5 mg/kg). The primary outcome was the success rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 36 publications
(50 reference statements)
3
58
0
Order By: Relevance
“…Satisfaction of both patients and endoscopist and patients’ willingness to repeat FB were higher in the ciprofol-remifentanil group than in the propofol-remifentanil group, which may also be due in part to the lower incidence of pain on injection. Inconsistent with the results of a previous study, the incidence of AEs, except pain on injection, was similar between the two groups ( Li et al, 2022 ). These differences may be due to small sample sizes in our trial and different anesthesia schemes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Satisfaction of both patients and endoscopist and patients’ willingness to repeat FB were higher in the ciprofol-remifentanil group than in the propofol-remifentanil group, which may also be due in part to the lower incidence of pain on injection. Inconsistent with the results of a previous study, the incidence of AEs, except pain on injection, was similar between the two groups ( Li et al, 2022 ). These differences may be due to small sample sizes in our trial and different anesthesia schemes.…”
Section: Discussionsupporting
confidence: 87%
“…Although the pharmacokinetic characteristics of 0.4 mg/kg of ciprofol are similar in elderly and non-elderly patients in some studies, this trial used 0.3 mg/kg of ciprofol to account for a variety of patient factors, procedure differences, and anesthesia schemes (especially the combination with remifentanil). Previous phase I–III clinical trials have reported that only 20%–25% of a ciprofol dose was needed to achieve the same anesthetic effect as propofol ( Hu et al, 2021 ; Li et al, 2022 ; Liu et al, 2022 ). Thus, this trial used 1.2 mg/kg propofol during anesthesia induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase III clinical trial was subsequently conducted in China to compare the effects of ciprofol and propofol on inducing deep sedation during gastroscopy ( n = 30) and colonoscopy ( n = 259) procedures [ 25 ]. In this trial, the success rate of colonoscopy was 100% in the ciprofol group and 99.2% in the propofol group (mean difference, 0.8%; 95% CI: 2.2% to 4.2%); the gastroscopy success rate was 100% in both groups.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…There were no significant differences between the two groups in terms of induction time (MOAA/S ≤ 1 after administration of the initial dose), insertion time, and insertion success rates. It is worth noting that the mean time for a patient to become fully alert in the ciprofol group was longer than the propofol group in the overall analysis, and the time to discharge of the ciprofol group was significantly longer than that of the propofol group (7.4 ± 3.1 min vs. 6.0 ± 2.1 min, P < 0.001), whereas patient satisfaction scores of the ciprofol group were significantly superior to that of the propofol group (9.9 ± 0.4 vs. 9.7 ± 0.7, P = 0.001) [ 25 ]. A larger number of subjects demonstrated ciprofol 0.4 mg/kg were noninferior to 1.5 mg/kg propofol in the success rate of gastroscopy or colonoscopy.…”
Section: Pharmacodynamicsmentioning
confidence: 99%